Studi Fenomenologi: Kebutuhan Dukungan Sosial pada Remaja dengan Diabetes Mellitus Tipe-1 - Dewi, Winasari (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
In every year, there was an increase in type-1 DM patients. Without adequate social support, type-1 DM often disrupted the normal life of the patients. The aim of this research is to explore social support needs for the adolescents with type-1 DM. The research using a qualitative methods with phenomenology. The number of participants in this research is 6 adolescents with type-1 DM. The sampling technique was used purposive sampling. Data analysis using thematic analysis. Result of this research is identified four themes: dependency with around people, controlled living, happiness when support was given, and desire like other adolescents. Based on the study findings, researcher recommended for pediatric nurse with others part can be coordinated to develop innovation for a review of nursing care provides nursing care with holistic and comprehensive for adolescents with type-1 DM so need of them for the social support can be fulfilled.